Cognitive status and influencing factors in maintenance dialysis patients with secondary hyperparathyroidism - LIU Gui-ling; LI Dan-dan; WANG Rui-feng; WANG Xue-rong; CHEN Xiao-li; HAO Li (Linchuang shenzangbing zazhi)
Objective To investigate the cognitive status and influencing factors in maintenance dialysis patients with hyperparathyroidism.Methods According to the level of parathyroid hormone and clinical symptoms,patients with duration of peritoneal dialysis ≥3 months were divided into PTH<630 ng/L group（group A,no-combined bone pain and skin itchy） and PTH >630 ng/L group（group B,combined bone pain and skin itchy）.Detailed history was asked and blood routine,biochemical routine,electrolytes,parathyroid hormone,and 25-dihydroxy vitamin D3 were determined.Cognitive function was assessed using the modified mini-mental assessment amount（3MS） table in a week after blood tests.The differences in gender,age,history of cerebrovascular disease,hemoglobin,serum creatinine,blood urea nitrogen,uric acid,albumin before,serum albumin,calcium,phosphorus,parathyroid hormone,25-hydroxy vitamin D3 and 3MS score were analyzed between two groups.The correlations between the 3MS score and other measurement indicators were analyzed.Results There was no significant difference（P>0.05） between two groups in the patient’s gender,age,history of cerebrovascular diseases,serum creatinine,blood urea nitrogen,uric acid,the former plasma albumin,and plasma albumia The levels of hemoglobin,serum calcium,25-hydroxyvitamin D3levels and 3MS scores in group A were significantly higher than in group B（P<0.05）.The levels of serum phosphorus and serum parathyroid hormone in group B were significantly higher than in group A（P<0.05）.In group A,correlation analysis showed that the 3MS score was negatively correlated with age,the history of cerebral vascular disease and parathyroid hormone levels.In group B,correlation analysis showed that the 3MS score was positively correlated with serum calcium and concentration level of 25-hydroxyvitamin D3,but negatively correlated with age,the history of cerebrovascular disease,serum phosphate levels and parathyroid hormone levels,and not with gender,hemoglobin concentration,serum creatinine,blood urea nitrogen,uric acid,pre-albumin and serum albumin level.Multivariate stepwise logistic regression analysis revealed statistically significant associations between3 MS and 25-hydroxyl vitamin D3（P = 0.000）,serum calcium（P = 0.002）,serum phosphate（P =0.089） and parathyroid hormone（P = 0.002）.Conclusions In the maintenance peritoneal dialysis patients with secondary hyperparathyroidism,the overall cognitive level is decreased significantly as compared with those without secondary hyperparathyroidism in peritoneal dialysis patients.The overall cognitive level in the maintenance peritoneal dialysis patients with secondary hyperparathyroidism has a relationship with gender,age,serum calcium and phosphorus,25-hydroxy vitamin D3 and parathyroid hormone levels.Correcting the metabolic disorders of calcium and phosphorus and reducing parathyroid hormone levels may be an important means to improve cognitive function in peritoneal dialysis patients with secondary hyperparathyroidism.